2013
DOI: 10.1063/1.4774241
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of intermediate band formation on titanium-implanted silicon

Abstract: Intermediate band formation on silicon layers for solar cell applications was achieved by titanium implantation and laser annealing. A two-layer heterogeneous system, formed by the implanted layer and by the un-implanted substrate, was formed. In this work, we present for the first time electrical characterization results which show that recombination is suppressed when the Ti concentration is high enough to overcome the Mott limit, in agreement with the intermediate band theory. Clear differences have been ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 16 publications
(16 reference statements)
1
26
0
Order By: Relevance
“…16 Other works report values of energy under 10 meV: Antonov et al found a MN energy of 6.9 meV in the diffusion of nanoclusters and islands on solid Xe. 17 The same group 18 studied nanoclusters and islands on CO 2 , obtaining a MN energy of approximately 9 meV, in agreement with the most active phonon band for solid CO 2 .…”
Section: -2mentioning
confidence: 73%
See 1 more Smart Citation
“…16 Other works report values of energy under 10 meV: Antonov et al found a MN energy of 6.9 meV in the diffusion of nanoclusters and islands on solid Xe. 17 The same group 18 studied nanoclusters and islands on CO 2 , obtaining a MN energy of approximately 9 meV, in agreement with the most active phonon band for solid CO 2 .…”
Section: -2mentioning
confidence: 73%
“…The main goal of these studies is the formation of an intermediate band (IB) in the midgap of the semiconductor to induce infrared absorption in this material. 1,2 This approach would enable electrons to be pumped from the valence band (VB) into conduction band (CB) via two-photon absorption with lower energy than the semiconductor band gap. 3 There are two main reasons why obtaining this target is so interesting.…”
mentioning
confidence: 99%
“…As it was assumed, occurrence of this new band could allow the photons of energy lower than E g to be absorbed, generating additional photocurrent and consequently, increasing the PV cells efficiency. The possibility of IB formation was confirmed experimentally for different impurities such as titanium [12], sulphur [13], selenium and tellurium [14]. Moreover, this may be be possible for other elements such as chalcogens or transition metals.…”
Section: Introductionmentioning
confidence: 57%
“…As it was pointed out, some of the recorded plots did not reveal symptoms of the existence of any deep levels. According to what was suggested in [12], such tendency coincides with the IB theory which assumes that recombination is suppressed when the IB band is formed. However, in order to confirm whether the intermediate band was actually formed, it is necessary to perform further analyses.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation